Altered Lipid Metabolism Impairs Skeletal Muscle Force in Young Rats Submitted to a Short-Term High-Fat Diet - Andrich, David E.; Ou, Ya; Melbouci, Lilya; Leduc-Gaudet, Jean-Philippe; Auclair, Nickolas; Mercier, Jocelyne; Secco, Blandine; Tomaz, Luciane Magri; Gouspillou, Gilles; Danialou, Gawiyou; Comtois, Alain-Steve; St-Pierre, David H. (Frontiers in Physiology, 2018)
Obesity and ensuing disorders are increasingly prevalent in young populations. Prolonged exposure to high-fat diets (HFD) and excessive lipid accumulation were recently suggested to impair skeletal muscle functions in rodents. We aimed to determine the effects of a short-term HFD on skeletal muscle function in young rats. Young male Wistar rats (100-125 g) were fed HFD or a regular chow diet (RCD) for 14 days. Specific force, resistance to fatigue and recovery were tested in extensor digitorum longus (EDL; glycolytic) and soleus (SOL; oxidative) muscles using an ex vivo muscle contractility system. Muscle fiber typing and insulin signaling were analyzed while intramyocellular lipid droplets (LD) were characterized. Expression of key markers of lipid metabolism was also measured. Weight gain was similar for both groups. Specific force was decreased in SOL, but not in EDL of HFD rats. Muscle resistance to fatigue and force recovery were not altered in response to the diets. Similarly, muscle fiber type distribution and insulin signaling were not influenced by HFD. On the other hand, percent area and average size of intramyocellular LDs were significantly increased in the SOL of HFD rats. These effects were consistent with the increased expression of several mediators of lipid metabolism in the SOL muscle. A short-term HFD impairs specific force and alters lipid metabolism in SOL, but not EDL muscles of young rats. This indicates the importance of clarifying the early mechanisms through which lipid metabolism affects skeletal muscle functions in response to obesogenic diets in young populations.